Catheter ablation in patients with atrial fibrillation and dilated cardiomyopathy - Siow, Yoon-Kee; Lin, Chin-Yu; Chung, Fa-Po; Lin, Yenn-Jiang; Chang, Shih-Lin; Lo, Li-Wei; Hu, Yu-Feng; Liao, Jo-Nan; Chang, Ting-Yung; Tuan, Ta-Chuan; Kuo, Ling; Wu, Cheng-I; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Catheter ablation is an effective and safe strategy for treating atrial fibrillation patients. Nevertheless, studies on the long-term outcomes of catheter ablation in patients with dilated cardiomyopathy are limited. Objective: This study aimed to assess the electrophysiological characteristics of atrial fibrillation patients with dilated cardiomyopathy and compare the long-term clinical outcomes between patients undergoing catheter ablation and medical therapy. Method: Patient baseline characteristics and electrophysiological parameters were examined to identify the predictors of atrial fibrillation recurrence following catheter ablation. The clinical outcomes of catheter ablation and medical therapy were compared using the propensity score matched method. Results: A total of 343 patients were enrolled, with 46 in the catheter ablation group and 297 in the medical therapy group. Among the catheter ablation group, 58.7% (n=27) had persistent atrial fibrillation. The recurrence rate of atrial arrhythmia was 30.4% (n=14) after an average follow-up duration of 7.7 years following catheter ablation. The only predictive factor for atrial fibrillation recurrence after catheter ablation was the left atrial diameter. When compared to medical therapy, catheter ablation demonstrated significantly better outcomes in terms of overall survival, freedom from heart failure hospitalization, improvement in left ventricular ejection fraction, and a greater reduction in left ventricular diameter and left atrial diameter after propensity score matching. Conclusions: Therefore, catheter ablation proves to be effective in providing long-term control of atrial fibrillation in patients with dilated cardiomyopathy. In addition to standard heart failure care, catheter ablation significantly enhanced both morbidity and mortality outcomes and reversed structural remodeling when compared to heart failure medication alone.